Enhancing Endothelial Differentiation of Mesenchymal Stem Cells Derived from Human Turbinates Using Lab-on-a-Chip Technology - Do Hyun Kim; Sang Hi Park; Mi-yeon Kwon; Chae-Yoon Lim; Sun Hwa Park; David W. Jang; Se Hwan Hwang; Sung Won Kim (Medicina)
Background and Objectives: Endothelial cells are essential to various therapeutic strategies for cardiovascular diseases. Developing efficient methods to generate large quantities of well-defined endothelial cells could improve cardiovascular treatment. This study explored the impact of lab-on-a-chip technology on the endothelial differentiation potential of mesenchymal stem cells derived from the human inferior nasal turbinate (hNTSCs). Materials and Methods: hNTSCs were isolated from five patients and divided into two groups: an experimental group subjected to lab-on-a-chip technology and a control group following two-dimensional differentiation protocols. The endothelial differentiation capacity of hNTSCs was assessed through histological examination and gene expression analysis. Results: Comparative evaluation of traditional differentiation methods and lab-on-a-chip technology indicated that hNTSCs expressed endothelial cell-specific markers, including CD34, KDR, CDH5, and CD31. Notably, CD31, CD34, and CDH5 exhibited significantly elevated expression levels in the lab-on-a-chip system. Additionally, cytokine analysis showed marked increases in IL-1a and IL-8 expression under lab-on-a-chip conditions compared to standard differentiation techniques. Conclusions: Lab-on-a-chip technology may enhance the differentiation of hNTSCs into endothelial cells with angiogenic potential, highlighting its promise for future cardiovascular regenerative applications.